Efficacy of granulocyte colony-stimulating factor for infertility undergoing IVF: a systematic review and meta-analysis - Lu-lu Fu; Ying Xu; Jing Yan; Xue-ying Zhang; Dan-dan Li; Lian-wen Zheng (BMC, 2023)
Abstract Objective This study aimed to evaluate the effectiveness of granulocyte colony-stimulating factor (G-CSF) for infertility and recurrent spontaneous abortion. Methods Existing research was searched in PubMed, Embase and Cochrane Library till Dec 2021. Randomized control trials (RCTs) that compared G-CSF administration with the control group in infertility women undergoing IVF were included. The primary outcomes included clinical pregnancy rate; the secondary outcomes included live birth rate, abortion ratebiochemical pregnancy rate, embryo implantation rate, as well as endometrial thickness. Result(s) 20 RCTs were included in this study. G-CSF increased the clinical pregnancy rate (RR = 1.85; 95% CI: 1.07, 3.18) and the endometrial thickness (MD = 2.25; 95% CI: 1.58,2.92;) in patients with thin endometrium undergoing IVF. G-CSF increased the biochemical pregnancy rate (RR = 2.12; 95% CI: 1.54, 2.93), the embryo implantation rate (RR = 2.51; 95% CI: 1.82, 3.47) and the clinical pregnancy rate (RR = 1.93; 95% CI: 1.63, 2.29) in patients with a history of repeated implantation failure undergoing IVF. No differences were found in pregnancy outcomes of general IVF patients. Conclusions Granulocyte colony-stimulating factor is likely to be a potential option for infertility women undergoing IVF with thin endometrium or recurrent implantation failure . Trial registration Retrospectively registered (The PROSPERO registration number: CRD42022360161).